Comparison of visual requirements and regulations for obtaining a driving license in different European countries and some open questions on their adequacy - Kobal, Nina; Hawlina, Marko (Frontiers in Human Neuroscience, 2022)
We reviewed the current state of knowledge regarding visual function and its suitability as part of medical examinations for driving licenses. We focused only on Group 1 drivers. According to previous studies, visual acuity, which is the most common test, is weakly associated with a higher risk of road accidents, with a greater role of visual field. The inclusion of the visual field test in medical examinations is therefore important, but the actual limit value is still unclear and further research in specific situations is needed. Color vision impairment was not found a threat to traffic safety. Contrast sensitivity decreases with age and is affected by abnormal eye conditions. Resulting glare can lead to an increased risk of traffic accidents during night driving in the elderly and others with conditions that impair contrast sensitivity. However, the universal cut-off limits have not been established either. The current European Union regulations therefore reflect minimum common denominator across the member states which may not entirely translate to optimal driving safety. Due to these open questions, standardized testing in simulators or on polygons that simulate real life conditions would be needed to better determine safe limits of visual function in different conditions. As there is a need to have better standardization across Europe regarding the requirements and rules regarding driving licenses in European countries, we first analyzed existing rules and compared them with each other, also in terms of deviations from the European Union directive itself. We reviewed the literature in this field and prepared proposals for a more optimal regulation of the rules in the future. Particular attention is paid to the new method of examining the visual field that was created to respect the European directive. The paper can serve as a basis of information for research teams to design further protocols, as it gathers research findings to date on the importance and impact of various visual functions on driving safety, as well as a starting point for a debate on revising existing rules for obtaining and maintaining licenses, as it compares the current regulations in European countries and differences between them.